2001
DOI: 10.2166/wst.2001.0792
|View full text |Cite
|
Sign up to set email alerts
|

Municipal wastewater sludge dewaterability and the presence of microbial extracellular polymer

Abstract: Dewatering of sewage sludge is an essential and costly part of the wastewater treatment process. The presence of microbial extracellular polymer (ECP) is important for sludge flocculation, but ECP has also been shown to have a detrimental effect on the dewaterability of certain sludge types. This paper investigates the relationship between sludge dewaterability and the level of ECP present in a range of sludges obtained from 8 full-scale municipal treatment works in the UK. Sludge dewaterability was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(84 citation statements)
references
References 0 publications
6
77
0
1
Order By: Relevance
“…Many previous studies have demonstrated that EPS was the most crucial deciding factor for sludge dewatering (Mikkelsen and Keiding, 2002;Niu et al, 2013;Chen et al, 2015). Houghton et al (2001) reported that the dewaterability was determined by the contents of EPS and there existed an optimal EPS content for each sludge, at this time, the sludge exhibited the best dewatering property. Many researchers found that proteins and polysaccharides ratios had more significant effect on sludge dewatering property (Higgins and Novak, 1997a).…”
Section: Introductionmentioning
confidence: 98%
“…Many previous studies have demonstrated that EPS was the most crucial deciding factor for sludge dewatering (Mikkelsen and Keiding, 2002;Niu et al, 2013;Chen et al, 2015). Houghton et al (2001) reported that the dewaterability was determined by the contents of EPS and there existed an optimal EPS content for each sludge, at this time, the sludge exhibited the best dewatering property. Many researchers found that proteins and polysaccharides ratios had more significant effect on sludge dewatering property (Higgins and Novak, 1997a).…”
Section: Introductionmentioning
confidence: 98%
“…Again, EPS content also greatly affected the charge property and floc stability (Mikkelsen and Keiding, 2002). Houghton et al (2001) found that there existed a certain EPS mass at which the sludge dewaterability reach the maximum (Houghton et al, 2001). Higgins and Novak (1997) demonstrated that the sludge dewaterability was mainly affected by the ratio of protein and polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution and chemical compostion of EPS had significant effect on sludge dewatering property [4,5]. Houghton found that the there existed a certain EPS mass at which the sludge dewaterability reach the maximum [6]. Again, EPS content also greatly affected the charge property and floc stability [4].…”
Section: Introductionmentioning
confidence: 99%